Editorial: Supply chain management - Dimitrios Aidonis; Dimitrios Folinas (International Journal of Business Science & Applied Management (IJBSAM), 2016)
This special issue has followed up the 3rd Olympus International Conference on Supply Chains held on Athens Metropolitan Expo, November 7 & 8 2015, Greece. The Conference was organized by the Department of Logistics Technological Educational Institute of Central Macedonia, in collaboration with the: a) Laboratory of Quantitative Analysis, Logistics and Supply Chain Management of the Department of Mechanical Engineering, Aristotle University of Thessaloniki (AUTH), b) Greek Association of Supply Chain Management (EEL of Northern Greece) and the c) Supply Chain & Logistics Journal. During the 2-Days Conference more than 60 research papers were presented covering the following thematic areas: (i) Transportation, (ii) Best Practices in Logistics, (iii) Information and Communication Technologies in Supply Chain Management, (iv) Food Logistics, (v) New Trends in Business Logistics, and (vi) Green Supply Chain Management. Three keynote invited speakers addressed interesting issues for the Operational Research, the Opportunities and Prospects of Greek Ports chaired Round Tables with other Greek and Foreign Scientists and Specialists.
Keywords: 650; 3rd Olympus International Conference on Supply Chains; special issue; selected papers